1994
DOI: 10.1007/bf02036184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coumarin and xanthotoxin on mitochondrial structure, oxygen uptake, and succinate dehydrogenase activity in onion root cells

Abstract: At concentrations in which they occur on the plant surface and retard mitosis, coumarin and xanthotoxin lowered uptake of oxygen (by 60 and 30%, respectively) by meristematic cells ofAllium cepa root tips. They caused changes in the structure of the mitochondrial matrix to become dense, and protrusions of mitochondrial membranes were visible parallelling their hypertrophy, indicating alteration in the structure and physiology of these organelles. Coumarin and, to a lesser extent, xanthotoxin increased succinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…It was not accom pa nied by any dis tur bances in chloroplasts or any other organellar struc tures, ex cept for slightly dis tended cristae of mi to chon dria (Galindo et al 1999). More ev i dent changes in the struc ture of mito chon dria in cells of api cal A. cepa root meristem were in duced by coumarins (Kupidłowska et al 1994a). Most of mi to chon dria be came con densed with elec tron dense ma trix and ex tended intracristal spaces.…”
Section: Cell Ultrastructurementioning
confidence: 96%
See 2 more Smart Citations
“…It was not accom pa nied by any dis tur bances in chloroplasts or any other organellar struc tures, ex cept for slightly dis tended cristae of mi to chon dria (Galindo et al 1999). More ev i dent changes in the struc ture of mito chon dria in cells of api cal A. cepa root meristem were in duced by coumarins (Kupidłowska et al 1994a). Most of mi to chon dria be came con densed with elec tron dense ma trix and ex tended intracristal spaces.…”
Section: Cell Ultrastructurementioning
confidence: 96%
“…In some organelles pro tru sions con tain ing frag ments of mem branes were formed as the re sult of hy per tro phy of mi to chon drial membranes. It was sug gested that dis tur bances of cell mem branes by coumarins were as so ci ated with the abil ity of these com pounds to re act with mem brane lipids or pro teins, re sult ing in changes of membrane per me abil ity and fi nally in mod i fi ca tion of en ergy pro duc tion (Kupidłowska et al 1994a). …”
Section: Cell Ultrastructurementioning
confidence: 98%
See 1 more Smart Citation
“…The overall reaction of biological nitrogen fixation (Van Kammen, 1995) from which we can see that nitrogenase enzyme activity requires large amounts of energy (ATP) is described below. Allelochemical effects on respiratory activity have been reported in corn (Koeppe, 1972;Abrahim et al, 2000;Abrahim et al, 2003a), soybean (Penuelas et al, 1996;Jose and Gillespie, 1998;Sert et al, 1998;Abrahim et al, 2003b), onion root tips (Kupidlowska et al, 1994), mycorrhizal fungi (Boufalis and Pellissier, 1994), and yeast mitochondria (Einhellig, 1995 and papers therein). Chaniago (2004) demonstrated that amaranth, nutgrass or paspalum extracts reduced respiratory activity of germinating soybean.…”
Section: Resultsmentioning
confidence: 99%
“…Coumarin inhibits cell elongation, cell division, differentiation, rhizogenesis and germination (Kupidlowska et al, 1994a), and promotes rooting in leaf explants of petunia (Abenavoli et al, 2001b). Coumarin and xanthotoxin stimulated the fragmentation of endoplasmic reticulum cisternae, decreased the number of dictyosomes and condensed the mitochondrial matrix indicating a possible energy shortage in the maize cell and cucumber plants while the garden pea was resistant (Francisco et al, 1991;Kupidlowska et al, 1994b).…”
Section: Coumarin As Cell Division and Cell Elongation Inhibitormentioning
confidence: 99%